Kualitas Hidup Pasien Gagal Ginjal yang Menjalani Hemodialisis - Rizky Firman; Sri Mugianti; Imam Sunarno; Sri Winarni (Journal of Ners and Midwifery, 2016)
Chronic renal failure (CRF) is a public health problem in the world and is now recognized as common diseases with risk of hemodialysis therapy. Hemodialysis can have an impact to the patient quality of life. The aim of the research was to describe the patient quality of life with renal failure underg hemodialysis at Mardi Waluyo Blitar hospital. The research used a descriptive research design. The population was all patients with renal failure which registered in Hemodialysis of Mardi Waluyo Blitar hospital on October-December 2014 as many as 84 patients. The sample was 34 patients selected by accidental sampling. The data collection was conducted on March 30th – April 4th, 2015. The data collecting used questionnaires of The World Health Organization Quality of Life (QoL WHO) which described physical health, psychological, social relationships, and environment. In general the quality life of renal failure patient underrgo hemodialysis in bad category was 55.9% (19 patients). This condition was due to a chronic disease and its complications potentially stressors including renal failure patient. Stressors that arise caused by environmental conditions, psychological state, and physical health. The study recommended that health services were expected to provide comfortability, improve maintenance functions, improve interpersonal relationships, and counseling.